Kspectrum: an open-source code for high-resolution molecular absorption spectra production. (January 2016) - Eymet, V.; Coustet, C.; Piaud, B.
Abstract: We present the kspectrum, scientific code that produces high-resolution synthetic absorption spectra from public molecular transition parameters databases. This code was originally required by the atmospheric and astrophysics communities, and its evolution is now driven by new scientific projects among the user community. Since it was designed without any optimization that would be specific to any particular application field, its use could also be extended to other domains. kspectrum produces spectral data that can subsequently be used either for high-resolution radiative transfer simulations, or for producing statistic spectral model parameters using additional tools. This is a open project that aims at providing an up-to-date tool that takes advantage of modern computational hardware and recent parallelization libraries. It is currently provided by Méso-Star (http://www.meso-star.com ) under the CeCILL license, and benefits from regular updates and improvements.